2019
DOI: 10.1002/ps.5533
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term field insecticide susceptibility data and laboratory experiments reveal evidence for cross resistance to other neonicotinoids in the imidacloprid‐resistant brown planthopper Nilaparvata lugens

Abstract: BACKGROUND: Long-term monitoring data is helpful to understand the fluctuation of susceptibility and pattern of cross resistance in insecticide resistance management. After the occurrence of imidacloprid resistance, the brown planthopper (BPH) has gradually developed resistance to thiamethoxam and clothianidin since 2010, but not to dinotefuran and nitenpyram. Here, we analyzed susceptibilities data of five neonicotinoids during 2005-2017 in East Asia and Vietnam to conduct cross-resistance patterns among neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…Imidacloprid‐resistant strains were collected in 2009 (VN09‐1 and VN09‐3) and 2010 (VN10‐1) in Vietnam and 2014 in the Kumamoto prefecture, Japan (KR‐14). VN09‐3_F 24 was the most resistant laboratory‐selected strain established from VN09‐3 with exposure to imidacloprid for 24 generations 20–22 . Izumo‐87♀ x VN09‐1♂_F 1 (IxV‐F 1 ) and Izumo‐87♂ x VN09‐1♀_F 1 (VxI‐F 1 ) were F 1 s of the VN09‐1 and Izumo‐87 strains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidacloprid‐resistant strains were collected in 2009 (VN09‐1 and VN09‐3) and 2010 (VN10‐1) in Vietnam and 2014 in the Kumamoto prefecture, Japan (KR‐14). VN09‐3_F 24 was the most resistant laboratory‐selected strain established from VN09‐3 with exposure to imidacloprid for 24 generations 20–22 . Izumo‐87♀ x VN09‐1♂_F 1 (IxV‐F 1 ) and Izumo‐87♂ x VN09‐1♀_F 1 (VxI‐F 1 ) were F 1 s of the VN09‐1 and Izumo‐87 strains.…”
Section: Methodsmentioning
confidence: 99%
“…VN09-3_F 24 was the most resistant laboratory-selected strain established from VN09-3 with exposure to imidacloprid for 24 generations. [20][21][22] Izumo-87♀ x VN09-1♂_F 1 (IxV-F 1 ) and Izumo-87♂ x VN09-1♀_F 1 (VxI-F 1 ) were F 1 s of the VN09-1 and Izumo-87 strains. All insects were reared on rice seedlings in a glass bottle (6.5 cm diameter, 18 cm height) covered with a cloth mesh at 26°C under a long-day photoperiod (16L:8D) without exposure to insecticides.…”
Section: Insectsmentioning
confidence: 99%
“…- Saeed et al (2018) found in Pakistan that there was very high resistance to acetamiprid (433-fold) and imidacloprid (173-fold) in the crop pest Dysdercus koenigii. -Fujii et al (2019) studied resistance in the brown planthopper in East Asia and Vietnam. Initially this was with imidacloprid, but this had spread to thiamethoxam and clothianidin, but not to dinotefuran and nitenpyram.…”
Section: Effectiveness and Alternativesmentioning
confidence: 99%
“…Currently, chemical control is the main measure implemented to prevent BPH outbreaks. Yet due to the excessive and unscientific use of insecticides, BPH has since developed resistance to many of them 6,7 . Cultivating resistant rice varieties is the most economical and environmentally friendly method to control BPH populations; however, this pest may gradually adapt and persist after being reared on resistant rice plants for multiple generations 8,9 .…”
Section: Introductionmentioning
confidence: 99%